Determination of lactate influx rates into erythrocytes after maximal exercise - Wahl, P.; Frese, S.; Zinner, C.; Lenzen, E.; Mester, J.; Bloch, W. (momentum e-journal, 2010)
The purpose of the study was to investigate the maximal lactate influx rate of erythrocytes (RBC) under physiological conditions. Methods: The effects of short term maximal cycling exercise on lactate distribution between plasma and RBC during recovery were investigated. Twelve elite cyclists performed a 30 s lasting maximal-effort exercise on a cycle ergometer adjusted to an isokinetic mode. Blood samples were taken before exercise, directly after and in minute-intervals during recovery to determine lactate concentrations [La] in whole blood, plasma and RBC. Results: The congestion of lactate per time unit in plasma exceeded the lactate influx capacity of RBC causing a significant decrease in the RBC-to-plasma lactate concentration ratio ([La]RBC/[La]plasma) from 0.54 +- 0.04 before exercise to 0.32 +- 0.03 directly after exercise. The maximal lactate influx rate of RBC was 1.64 +- 0.45 mmol*L-1 in 30 s. If we assume a linear development of RBC [La] in the first minute we get an increase of 3.28 +- 0.45 mmol L-1*/min.